Sulfated Zirconia as an Efficient Catalyst for Sulfonylamidomethylation of Benzylsulfonamides and 2-Phenylethanesulfonamides: Effect of Catalyst Thermal Treatment - Sasiambarrena, Leandro Daniel (2010)
The synthesis of 3,4-dihydro-1H-2,3-benzothiazine2,2-dioxides and 1,2,4,5-tetrahydro-3,2-benzothiazepine3,3-dioxides is studied using sulfated zirconia ascatalyst. The sulfated zirconia calcined at 550ºC achieveda high selectivity which is attributed to the formation of atetragonal phase. In addition, the catalyst can be reused upto three times without loss of its catalytic activity.